2022
DOI: 10.1002/aenm.202270029
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Substitution in Ni‐Rich NMC Layered Cathodes for High‐Energy Lithium Ion Batteries (Adv. Energy Mater. 8/2022)

Abstract: Li‐Ion Batteries In article number 2103045, Aurora Gomez‐Martin, Richard Schmuch, and co‐workers report the effect of Mg substitution on mitigating the structural challenges of Ni‐rich layered oxide cathode materials upon cycling in lithium‐ion batteries. While partial substitution of Mg in Li sites linearly reduces the initial capacities at a given upper cut‐off cell voltage, the attainable cycle life is significantly extended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…State‐of‐the‐art (SOTA) cathode active materials (CAMs) are LiFePO 4 (LFP) and layered oxides such as LiNi 1‐ x‐y Co x Mn y O 2 (referred to as NCM xyz ; x + y + z =1) [3,4] . By increasing the Ni content within NCM materials, the energy density on material level can be gradually increased [1,5] .…”
Section: Introductionmentioning
confidence: 99%
“…State‐of‐the‐art (SOTA) cathode active materials (CAMs) are LiFePO 4 (LFP) and layered oxides such as LiNi 1‐ x‐y Co x Mn y O 2 (referred to as NCM xyz ; x + y + z =1) [3,4] . By increasing the Ni content within NCM materials, the energy density on material level can be gradually increased [1,5] .…”
Section: Introductionmentioning
confidence: 99%
“…Although NMC 750 °C shows good cycling stability, the achieved discharge capacity of 185 mAh/g at 20 °C and 0.1 C (18 mA/g), in a voltage window of 3.0‐4.3 V, is low compared to earlier reported results. Initial capacities above 200 mAh/g at 19–25 °C have been reported for Ni‐rich layered oxides with 85–90 at% Ni‐content [3,6,43,64,65] . Higher capacities have also been reported with lower Ni‐contents as well, such as above 190 mAh/g at 80 at% Ni [3,37,66–69] .…”
Section: Resultsmentioning
confidence: 96%
“…Several studies have observed that incorporating Al 3+ in NMC to form NMCA has improved the cycle life, [36–38] and Al 3+ has been reported to suppress the H2‐H3 phase transition associated anisotropic volume change [39,40] . Nb 5+ and Mg 2+ are other doping elements that have been explored to counteract the instability issues of Ni‐rich NMC [41–43] . As the Ni‐content increases there is correspondingly less substitutional freedom, and which supporting elements to include should be carefully considered due to their differing properties.…”
Section: Introductionmentioning
confidence: 99%
“…This helps explain the slightly larger presence of shattered particles from the LNO samples compared to the NBM samples, as continual cycling of these cracked particles can cause further mechanical pulverization from anisotropic lattice distortions typically seen with high‐Ni cathodes. [ 48,65 ]…”
Section: Resultsmentioning
confidence: 99%
“…The choice of Mg and B as dopants stems from the current understanding of Mg 2+ functioning as an inert pillaring ion in the Li layer to mitigate lattice collapse due to anisotropic distortions coupled with B promoting a robust microstructure and cathode‐electrolyte interphase (CEI) formation during cycling. [ 37,40–49 ] The NBM cathode exhibits a notable improvement in cycling stability with a 20% capacity retention increase over the baseline LNO cathode after long‐term cycling in pouch full cells. Hybrid pulse power characterization (HPPC) tests coupled with postmortem electrochemical, X‐ray diffraction (XRD), and scanning electron microscopy (SEM) analyses indicate more severe active Li loss present in the LNO cathode and less utilization in the graphite anode.…”
Section: Introductionmentioning
confidence: 99%